(untitled) (Advances in Applied Mathematics and Mechanics, 2019)
Double-step interrogation schemes with decreasing window size are investigated. Particle image pairs are created by Monte Carlo methods based on a simulated hypersonic transitional boundary layer flow. Two types of initial-step interpolation, with and without non-slip conditions at the wall (so-called CSIN and CSI), are respectively investigated. It can be concluded that the non-slip condition is very important to the multi-grid interrogation scheme. CSIN has a good agreement with the preset results but CSI does not.00a0 The error level of CSI near the wall is nearly 5 times that of CSIN.